Affordable Care Act did not reduce inappropriate use of emergency room services. (30th September 2020) - DeLellis, N; Wilson, F; Belsito, F; Cunningham, W
Abstract: Background: The US Patient Protection and Affordable Care Act of 2010 (ACA) has several provisions to increase access to health insurance among Americans. Prior to ACA, emergency departments (ED) served as a safety net to uninsured as most hospitals are required to provide stabilizing treatment to patients with emergency medical conditions regardless of their ability to pay. The ACA increased the number of insured, improved access to primary care and was expected to reduce high cost ED utilization Methods: This retrospective cross-sectional study used ED data from a US Midwest suburban medium size hospital (November 2009 - January 2017) to analyze the patterns of ER utilization pre- and post-ACA. The data (n = 423, 548) excluded ambulance deliveries; 5-level Emergency Severity Index was re-coded as urgent/non-urgent for each visit. Analysis included age, sex, race, mode of arrival, disposition, insurance, visit day and time as other predictors in binary logistic regression. Results: Non-urgent visit proportion increased from 34.5% in 2009 to 49.1% in 2016; odds of a visit being urgent are lower after ACA (Exp(B)=0.684; 95%CI 0.675, 0.694) with stronger effect for pediatric (age<18) population (Exp(B)=0.487, CI 0.471, 0.503). ACA did not change ED utilization by working population, however, in comparison to people with commercial insurance, patients without recorded insurance are less likely to have a true urgent visit (Exp(B)=0.845; CI 0.83, 0.86). Among other factors predicting ED visit urgency are race and insurance type. Conclusions: Expensive ER care is still provided for non-urgent care. Access to alternative type of care and public health awareness efforts should focus on subpopulations with high inappropriate ED use. Key messages: Affordable Care Act (2010) did not improve efficiency of emergency room utilization. Additional effort are needed to increase access to primary care and awareness of ER use for specific subpopulations.